Sobre a leucotomia pré-frontal de Egas Moniz - Mario Yahn (Arquivos de Neuro-Psiquiatria)
This paper is based on a review of 209 female patients admitted to the 5th. Pavillion, at the Juqueri State Hospital, São Paulo, Brazil, observed between February 1936 anti December 1945. One hundred and sixty-one patients were operated on by the Egas Moniz's method of leucotomy and 48 by the Freeman and Watts's technique of prefrontal lobotomy. Since January 1946, we are performing the Freeman and Watts's prefrontal lobotomy in three stages for the purpose of determining the effets of incisions in different parts of the prefrontal region as regards mental condition. The available data about this subject are not sufficient to warrant any conclusion and are not discussed here. The majority of our patients were chronic schizophrenics already treated by two or more of the most recent shock therapy methods. The operations were performed by the chief neurosurgeon Dr. A. Mattos Pimenta and his assistants Drs. A. Sette Junior and A. C. Barretto. The results of the Egas Moniz's leucotomy are listed as follows: Schizophrenia (135 cases) - failures (108), complete or social recovery (21), deaths (2), improved (4); Feeble minded with other symptoms as prolonged episodes, excitement states (13 cases) - failures (7), complete recovery (5), improved (1); Manic-depressive psychosis (5) cases) - failures (3), complete recovery (2) psychopathic personality (3 cases) - failure (1), improved (1), complete recovery (1); Severe neurosis (2 cases) - complete recovery (2); Dementia paralytica (1 case) - improved (1); Encephalitis sequellae (2 cases) - improved (1), greatly improved (1). The results of the Freeman and Watts's prefrontal lobotomy are charted as follws: Schizophrenia (45 cases) - complete or social recovery (3), improved (2), failures (39), deaths (1); Typhoid encephalitis sequellae (1 case) - unchanged; Chrome mania excitation (1 case) - unchanged; Psychopathic personality (1 case) - unchanged. It is important to note that in 30 schizophrenic patients out of 45 subjected to Freeman and Watts's prefrontal lobotomy, Egas Moniz's leucotomy had failed. One in this group had social recovery after lobotomy and the two others greatly improved, what performs 10 percent of good results over the total number of operated patients. The results in the 15 schizophrenics whom only the prefrontal lobotomy was performed on are following: 1 death, 2 complete or social recovery (14 percent) .and 12 failures. We fell to be of value to compare the incidence of 10 per cent of patients influenced by the Egas Moniz's leucotomy plus Freeman and Watts's operation to that of 14 per cent influenced by the Freeman and Watts's prefrontal lobotomy alone and to that of 18 per cent influenced by the Egas Mofliz's leucotomy alone. The differences in these results may be explained by the unequal deal of the material among the various groups, which warrants only a relative value to the conclusions based on the comparison of those data. One of the deaths occurred at the 22nd hour after the operation ami necropsy revealed cerebral hemorrhage. The other death was due to kystic purulent meningitis, as proved by necropsy. This paper affords us an opportunity to show a table comparing the results obtained in the treatment of schizophrenia by several methods as metrazol, electroshock, insulin and cerebral leucotomy. This table (quadro 1) has been presented at the Congress of Neurology and Psychiatry, met in Buenos Aires at November, 1944. The table discloses the kind of our material, composed mainly by chronic patients, and points out psychosurgery's possibilities too. As may be noted, 155 of the 835 schizophrenic patients were less than 13 months ill; an incidence of 18,5 per cent of acute and subacute cases results. It is equally important to note that the illness time of 190 (or 23 per cent) is unknown, what is explained by the fact that a great number of our inmates are abandoned indigents, met in the streets and sent to this State Hospital by the police, thus causing us a great lack of data. It is useles for the scant material, a statistical analysis of the other groups. The criteria for diagnosis of schizophrenia and our concept concerning the evaluation of complete or social recovery are not discussed, as this subjetc has been already covered by us and Dr. Mariz de Oliveira Netto in a previous paper where the statistical results of the first 400 cases treated by von Meduna's method are reviewed. We used to apply to our patients a series of 20 convulsive shocks or insulin comas, at least. Only in the case of early recovery the series was not completed. Although 209 patients were operated on till the end of 1945, as stated, previous by only 93 who were operated on up to end of 1943 are included in this table, because the others have not been followed up as sufficiently yet. As for time of illness only the groups comprising a number of cases sufficiently observed are suitable to be compared. In the group ranging from 0 to 6 months, only 40 cases subjected to metrazol and 27 to insulin are considered, for those treated by electroshock therapy were very few in number. The rate of recoverries was 77 per cent with insulin and 45 per cent with metrazol. In the group ranging from 7 to 12 months of illness, 40 cases treated by metrazol and 30 subjected to insulin therapy are compared. The rate of recoveries with insulin is the same as in the anterior group (77 per cent) while that of metrazol decreased to 20 per cent. In this group are already included 2 patients treated by leucotomy, one of them recovered. This conforms to our previous statement that we used to apply leucotomy only to patients for whom other methods of treatment failed. Again the group including patients whose time of illness ranges from 13 to 18 months is not discussed on account of the little amount of cases. The next group, the largest of our estatistics, including chronic patients more than 13 months ill, is more interesting. Therein the incidence of recoveries was 22 per cent with insulin therapy, the largest as compared to that obtained with other methods. The leucotomy comes second, with 10 per cent of recoveries. It is amazing the result of analysis of the uninfluenced cases in this group. The rate of failures was 50 per cent with insulin, 69 per cent with metrazol, 82 per cent with electroshock and 83 per cent with leucotomy, which in this comparison comes as the last. But we must remember that the Egas Moniz's operation was carried out only on patients whose severe mental condition was not changed by other treatments. We wish to emphasize that before undergoing leucotomy, chronic schizophrenic patients altready treated by all the methods available were considered clinically hopeless cases. These data show also the value of the insulin therapy for chronic cases as compared to other methods. The incidence of mortality was 7 per cen«t with insulin, 3 per cent with electroshock and 1 per cent with leucotomy. We fell of interest to note the low incidence of fatalities with leucotomy as compared to that of 7 per cent with insulin therapy. This high incidence of fatalities in our clinical material, as confronted to those reported in the world literature (5 per cent) is due to the fact that here are included our earlier cases, treated in 1936, when we were tentatively applying the Braunmüll's technic of prolonged comas for the extremely severe cases. The only tabulated death with leucotomy was due to operative hemorrhage as stated before. At last, we wish to emphasize the rate of 14 per cent of recoveries and 6 per cent of great improvements performed by leucotomy, notwithstanding the poor conditions of the material so treated. Simple leucotomy quieteness and other minor changes behavior without any alteration in the structure of the psychosis are not considered. Inasmuch an easy, unexpensive and nearly dangerless method of treatment, leucotomy is doubtless apt to improve the conditions of the chronic patients. This was one of the reasons that induced us to carry out the psychosurgical method of treatment.